2021
DOI: 10.1371/journal.ppat.1009454
|View full text |Cite
|
Sign up to set email alerts
|

Effector and regulator: Diverse functions of C. elegans C-type lectin-like domain proteins

Abstract: In C. elegans, 283 clec genes encode a highly diverse family of C-type lectin-like domain (CTLD) proteins. Since vertebrate CTLD proteins have characterized functions in defense responses against pathogens and since expression of C. elegans clec genes is pathogen-dependent, it is generally assumed that clec genes function in C. elegans immune k. However, little is known about the relative contribution and exact function of CLEC proteins in C. elegans immunity. Here, we focused on the C. elegans clec gene clec-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 87 publications
(69 reference statements)
1
34
0
Order By: Relevance
“…Because clec-47 expression in C. elegans is associated with bacterial infection, we evaluated whether the purified MBP–CLEC-47–His protein demonstrated direct antimicrobial activity. Recombinant MBP–CLEC-47–His was utilized in the MIC assay, which was performed using the broth dilution method ( 11 , 31 ). However, recombinant CLEC-47 demonstrated no antimicrobial activity against E. faecium (Gram positive), S. aureus (Gram positive), K. pneumoniae (Gram negative), A. baumannii (Gram negative), P. aeruginosa (Gram negative), or K. aerogenes (Gram negative) up to the highest concentration tested (16 μg/ml) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because clec-47 expression in C. elegans is associated with bacterial infection, we evaluated whether the purified MBP–CLEC-47–His protein demonstrated direct antimicrobial activity. Recombinant MBP–CLEC-47–His was utilized in the MIC assay, which was performed using the broth dilution method ( 11 , 31 ). However, recombinant CLEC-47 demonstrated no antimicrobial activity against E. faecium (Gram positive), S. aureus (Gram positive), K. pneumoniae (Gram negative), A. baumannii (Gram negative), P. aeruginosa (Gram negative), or K. aerogenes (Gram negative) up to the highest concentration tested (16 μg/ml) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of recombinant protein in vitro was determined using the broth dilution method ( 11 , 31 ). Bacteria were cultured overnight and diluted to 5 × 10 5 CFU/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that some of the nematode's expanded repertoire of 283 C-type lectin-like domain (CTLD) proteins might be involved in microbial detection (Pees et al 2016;, especially as at least two of them can direct bind bacteria (Miltsch et al 2014). Generally, however, although several CTLD proteins do play a role in resistance to infection, this appears not to involve direct pathogen recognition (Pees et al 2017(Pees et al , 2021Yunger et al 2017).…”
Section: Recognising Infectionmentioning
confidence: 99%
“…Down syndrome cell adhesion molecule (Dscam) of Drosophila have the potential to express more than 18,000 isoforms of the immunoglobulin (Ig)-superfamily receptor ( 40 ). Similarly, the C-type lectin-like domain (CTLD) of C. elegans and fibrinogen-related proteins (FREPs) in the Pacific oyster Crassostrea gigas have diversity at nucleotide and protein levels ( 41 , 42 ). Hemocyanin (HMC) is a large copper-containing respiratory protein found in the hemolymph of mollusks and arthropods.…”
Section: Discussionmentioning
confidence: 99%